2007
DOI: 10.1590/s0100-879x2006005000184
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diphtheria and tetanus antibodies and circulation of Corynebacterium diphtheriae in São Paulo, Brazil

Abstract: The introduction of routine vaccination against tetanus and diphtheria in Brazil has decreased the incidence and changed the epidemiology of both diseases. We then investigated the prevalence of Corynebacterium diphtheriae carrier status and diphtheria and tetanus immunity in São Paulo, Brazil. From November 2001 to March 2003, 374 individuals were tested for the presence of C. diphtheriae in the nasooropharynx and of serum diphtheria and tetanus antibodies. Participants were all healthy individuals without ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
7
1
4
Order By: Relevance
“…Embora disponível na rede pública de saúde, a cobertura vacinal antitetânica ainda é bastante deficiente no Brasil, principalmente na população de idosos. Em estudo conduzido na Cidade de São Paulo observou-se que nos indivíduos maiores de 40 anos a prevalência de anticorpos protetores contra tétano é de apenas de 60% 11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora disponível na rede pública de saúde, a cobertura vacinal antitetânica ainda é bastante deficiente no Brasil, principalmente na população de idosos. Em estudo conduzido na Cidade de São Paulo observou-se que nos indivíduos maiores de 40 anos a prevalência de anticorpos protetores contra tétano é de apenas de 60% 11 .…”
Section: Discussionunclassified
“…O tétano acidental no Brasil apresenta uma tendência à senilização, visto a menor cobertura vacinal e a maior suscetibilidade aos acidentes na população geriátrica 11,12 . O coeficiente de mortalidade vem apresentando redução em todas as faixas etárias exceto nos maiores de 60 anos 13 .…”
Section: Discussionunclassified
“…A study investigating human immunity to DT in São Paulo (2001 to 2003) showed that 82% of individuals aged 40 to 59 years were susceptible to the disease (19). Overall, these data suggest that five years after the Brazilian Ministry of Health recommended additional booster doses to be provided every 10 years, the adult population in our country is not fully protected against diphtheria.…”
Section: Discussionmentioning
confidence: 78%
“…Taşıyıcılarda yeterli sayıda toksijenik suş ortaya çıktığında enfeksiyonun duyarlı kişilere yayılması artmaktadır. Avrupa'da yapılan çalışmalar, difteri epidemisini önlemek için gereken antikor düzeyinin popülasyonda koruyucu eşiğin altında olduğunu ve yaşla ters orantılı olarak azaldığını göstermektedir 9 .…”
Section: Discussionunclassified